PERAN KOMPETENSI SOSIAL GURU TERHADAP HUBUNGAN GURU DAN PESERTA DIDIK DI SLB NEGERI 1 BANTUL - Kuswarini; Saniyyah Difta P; Micky Arda Julanda; Dzakiyah Khansa; Dhiniaty Gularso (STKIP Subang, 2026)
This study aims to analyze the role of teachers’ social competence in shaping the relationship between teachers and students with physical disabilities at SLB Negeri 1 Bantul using a qualitative descriptive approach through non-participant observation and documentation methods. The findings indicate that teachers’ social competence plays a crucial role in creating effective learning processes and positive interpersonal relationships, as reflected in adaptive communication skills, empathy, patience, and the use of flexible teaching methods tailored to students’ needs. In addition, teachers contribute to fostering students’ social interaction and creating an inclusive learning environment, which positively impacts students’ comfort, self-confidence, learning motivation, as well as their social and emotional development. Overall, teachers’ social competence significantly contributes to the quality of learning in special education settings; therefore, continuous efforts through training and professional development are needed to improve the quality of educational services for students with special needs.